http://tru.uni-sz.bg/tsj/Vol15_N2_2017/Iv.Zarkov.pdf - T. K. Ojediran; T. O. Oloruntade; B. Y. Durojaye; R. O. Saka; I. A. Emiola (Trakia Journal of Sciences)
One hundred and fifty day-old Abor-acre strain broilers chicks were used to evaluate the blood parameters, carcass yield, organ weight and villi morphometrics of broilers fed low protein diet in excess of dietary lysine. The chicks were weighed on the eight day and then randomly assigned to five experimental diets in such a way that each dietary treatment had 30 birds replicated thrice. Diet 1 was the control with 22.22% crude protein (CP) while diets 2, 3, 4 and 5 contained 16.6% CP each at both starter and finisher phases with varying levels of lysine ranging from 0.50 to 0.90%. They all had the same level of methionine. Results showed that the birds fed diet 4 (16.6% CP and 0.8% lysine inclusion level) had a significantly (p<0.05) higher breast, villi height, crypt depth and muscle thickness while the lymphocyte count, total protein, abdominal fat and back size increased linearly with lysine inclusion unlike decreases in heterophil among birds fed LCP diets. It can be concluded that increased villi morphology enhanced breast yield due to enhanced absorption with increased abdominal fat as observed in birds fed 16.6% CP and 0.8% lysine inclusion level